Short-term Focused Feedback: A Model to Enhance Patient Engagement in Research and Intervention Delivery - Sauers-Ford, Hadley (Med Care, 2021)
Our grant from the Patient-Centered Outcomes Research Institute (PCORI) focused on the use of nurse home visits postdischarge for primarily pediatric hospital medicine patients. While our team recognized the importance of engaging parents and other stakeholders in our study, our project was one of the first funded to address transitions of care issues in patients without chronic illness; little evidence existed about how to engage acute stakeholders longitudinally. OBJECTIVE: This manuscript describes how we used both a short-term focused feedback model and longitudinal engagement methods to solicit input from parents, home care nurses, and other stakeholders throughout our 3-year study. RESULTS: Short-term focused feedback allowed the study team to collect feedback from hundreds of stakeholders. Initially, we conducted focus groups with parents with children recently discharged from the hospital. We used this feedback to modify our nurse home visit intervention, then used quality improvement methods with continued short-term focus feedback from families and nurses delivering the visits to adjust the visit processes and content. We also used their feedback to modify the outcome collection. Finally, during the randomized controlled trial, we added a parent to the study team to provide longitudinal input, as well as continued to solicit short-term focused feedback to increase recruitment and retention rates. CONCLUSION: Research studies can benefit from soliciting short-term focused feedback from many stakeholders; having this variety of perspectives allows for many voices to be heard, without placing an undue burden on a few stakeholders.